Study of the efficiency of an intervention program for of the ability to handle mobile primary - N. Ureña; F. Ureña; A. Velandrino; F. Alarcón (Asociación Española de Ciencias del Deporte, 2010)
The objectives of this research were to test the effectiveness of an intervention program to improve the ability to handle mobile objects in primary school students and validate the use of an qualitative assessment tool to find out about different levels of difficulty. Two hypothesis are under study: a) the program will improve the skill level of the students and b) the scale of motor tasks is an appropriate tool for its evaluation. We worked with a sample of 148 students from Primary School and used a pretest-postest design with a control group and two observations after the application of the program. We applied a scale of 15 tasks for the assessment of the ability to handle mobile objects. In the application phase was implemented an intervention program for the improvement of the skills being studied within the experimental group was implemented. The results indicated that the scale was an appropriate tool to assess the degree of difficulty of the tasks. In addition, it obtained a high retention level,  in all tasks regarding the experimental group one month after the program application. The most important is that the intervention program is offered as a valid alternative methodology to improve those skills. Key Words: program, basic abilities, scale, primary school.